Gambaran Kesehatan Mental Cleaning Service Di Universitas Negeri Gorontalo - Sutri DJ Eksan; Ika Wulansari; Cindy Puspita Sari Haji Jafar (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Mental health is a crucial aspect of life that affects a person's ability to think, feel, act, cope with problems, and overall quality of life; cleaning service workers at universities play a critical role in maintaining a clean and comfortable campus environment, yet their mental health remains understudied. This study aims to describe the mental health status of cleaning service workers at Universitas Negeri Gorontalo. This research employed a quantitative descriptive design with a total population of 241 cleaning service workers. A sample of 71 respondents was selected using accidental sampling technique, and data were collected using the Mental Health Inventory (MHI) questionnaire. Data were analyzed using univariate analysis. The results showed that the majority of respondents (57 respondents, 80.3%) were in the psychological well-being category, while 14 respondents (19.7%) were in the psychological distress category. These findings indicate that most cleaning service workers at Universitas Negeri Gorontalo have good mental health, although a notable minority experiences psychological distress. This study is expected to provide useful information to support mental health awareness and intervention among cleaning service workers at the university.